2006
DOI: 10.19030/tlc.v3i12.1653
|View full text |Cite
|
Sign up to set email alerts
|

Academic Success Of Non-Traditional Students: Factors Affecting Performance In An Upper-Division Undergraduate Accounting Course

Abstract: Many assessment activities are conducted within the context of AACSB International reaffirmation of business programs. Central to the AACSB evaluation process is assurance of learning standards. Learning goals vary among institutions because of differences in mission, faculty expectations, and student body composition. The objective of this research is to determine the factors that influence the academic performance of students in upper-level accounting courses and to assess student performance against course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The results are consistent to previous studies (Bouillon and Smith, 1991;Al-Tamimi and Al-Shayeb, 2002;Lynn and Robinson-Backmon, 2006) where they showed that students with high CGPA have better score in their performance. However, the results of this study contradict with Tay (1994).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The results are consistent to previous studies (Bouillon and Smith, 1991;Al-Tamimi and Al-Shayeb, 2002;Lynn and Robinson-Backmon, 2006) where they showed that students with high CGPA have better score in their performance. However, the results of this study contradict with Tay (1994).…”
Section: Resultssupporting
confidence: 92%
“…Studies that have examined this issue produced mixed results. There are studies that supported the hypothesis that CGPA is an important determinant to students' performance (such as Bouillon and Smith, 1991;Al-Tamimi and Al-Shayeb, 2002;Lynn and Robinson-Backmon, 2006). Other studies found negative relationship between CGPA and students' performance (Tay, 1994).…”
Section: Cumulative Grade Point Average (Cgpa) and Students' Performancementioning
confidence: 96%
See 3 more Smart Citations